2011
DOI: 10.3126/nje.v1i2.5091
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunization Status of Children between 12-23 months in Bareilly District

Abstract: ObjectivesTo assess the immunization status of children in the age group 12-23 months and to know the reasons for nonimmunization of children. Materials and MethodsA cross-sectional survey was conducted using WHO's thirty cluster sampling technique in rural and urban areas of Bareilly district from August 2008 to January 2009. Rural areas were divided into blocks and blocks were divided into villages. Urban areas were divided into wards. Villages and wards were taken as clusters. During the house-to-house surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…12 or 3.9% of respondents also blamed the unsatisfactory services provided by the clinic. This supports the study of Joshi et al [21] where they acknowledged that one of the biggest factors ofany healthcare facility's success is patient satisfaction. Also, 13 or 4.2% of respondents stated that their defaulting immunization was due to the inadequate information provided to them about immunization by the healthcare providers, while 21 (6.9%) respondents said that they were overseas at that time.…”
Section: Reasons For Parents For Defaulting Child Immunizationsupporting
confidence: 86%
“…12 or 3.9% of respondents also blamed the unsatisfactory services provided by the clinic. This supports the study of Joshi et al [21] where they acknowledged that one of the biggest factors ofany healthcare facility's success is patient satisfaction. Also, 13 or 4.2% of respondents stated that their defaulting immunization was due to the inadequate information provided to them about immunization by the healthcare providers, while 21 (6.9%) respondents said that they were overseas at that time.…”
Section: Reasons For Parents For Defaulting Child Immunizationsupporting
confidence: 86%
“…In a present study, 52% children were fully immunized, which is similar with a study conducted by Joshi et al [6] where 50% children were fully immunized. Findings of the current study is in between data of NFHS-III, which shows 40.1% children in rural area and coverage evaluation survey 2009 [7] shows 56.6% children were fully immunized.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is comparable to a finding from a study conducted in Debre markos town, Amhara Regional State, Ethiopia which reported the overall dropout was 5% (Gualu et al, 2017). The finding is lower from a report from a study conducted in Bareilly District 37.3% (Joshi et al, 2011). This might be related to the difference in the delivery of the service in the two study areas.…”
Section: Discussionsupporting
confidence: 58%